LITERATURE REVIEW ON THE EFFECT OF GOVERNMENT POLICIES ON THE STATUS OF HONORARY TEACHERS - Sa'i Sa'i (Indonesian Journal of Education (INJOE), 2025)
This literature review aims to analyse the influence of government policies on the status of honorary teachers in Indonesia. The results show that although policies such as the appointment of honorary teachers as civil servants, certification programmes, and the provision of professional allowances have provided opportunities for improving the status and welfare of some honorary teachers, their implementation still faces significant challenges. Budget limitations, regulatory inconsistencies and disparities between regions are the main obstacles. As a result, many honorary teachers still face status uncertainty, low income and lack of social security. The study also identifies the impact of these conditions on honorary teachers' motivation, performance and professionalism, and the implications for education quality. Based on the analysis, more comprehensive and sustainable policy reforms are recommended, including simplifying the appointment process, increasing the budget, improving the recruitment system, and developing alternative career paths for honorary teachers. Strengthening coordination between central and local governments is also emphasised to ensure more effective and equitable policy implementation.